Strategi Pengendalian Persediaan Kantong Semen dengan Integrasi Metode Activity Based Costing (ABC) dan Min-Max - Ayu Puspa Wirani; Steela Apfiasari; Octoberry Julyanto; Fakhri Fadhlurrahman (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The supply of cement bags in warehouses often experiences excess (overstock) due to differences between demand and use of cement bags in the packaging process. The number of cement bags used is lower than demand, causing stock differences. Based on this, it is necessary to carry out research regarding strategies for controlling cement bag inventory in companies. This aims to analyze the condition of the cement bag inventory in the warehouse, identify remaining unused cement bag stock, and calculate the Total Inventory Cost incurred by the company. In this research, the ABC and Min-Max methods were used. The ABC method is used to control a small number of goods, but has a high investment value. Meanwhile, the Min–Max method is used to determine the maximum and minimum inventory quantities to prevent stock shortages or excesses. The research results show that the actual average usage for 40 kg and 50 kg cement bags is 56.8% and 51.95% of the total inventory of cement bags, respectively. This means that the number of unused cement bags is very large and affects the costs incurred by the company. The total inventory cost incurred based on company policy for a 40 kg bag of cement is IDR 69,696,000 and 50 kg is IDR 78,874,592. Meanwhile, using the Min-Max method calculation, the Total Inventory Cost for a 40kg bag of cement is Rp. 33,157,552 and Rp. 36,312,692 for a 50kg cement bag.